Literacy voluntary teaching for low socio-economic early graders in Sumbawa Regency of Indonesia - Iwan Jazadi; Elli Marliana; Dita Rezkia Utami; Aris Dwi Intan Aprianti; Jalaluddin Jalaluddin; Solihin Solihin (International Journal of Evaluation and Research in Education (IJERE), 2023)
The research reported on a literacy intervention program for 150 early grade learners from low socio-economic background by involving 50 volunteers in 50 different village spots in Sumbawa Regency of Indonesia. The research was emancipatory because it seeks to empower the community to address the local problems of literacy learning loss experienced by the needy early graders. The data were collected through literacy assessment, observation, interviews, and documentation. The findings showed that 90% of the early graders improved their literacy mostly with two and one level progress. Factors contributing to the success were good preparation of volunteers, engaging teaching approaches, relevant materials that suited student levels, and continuous assessment. The last key finding was that the volunteers strongly embodied teaching voluntarism as a soul with six features (affection towards others, action of giving, availability, positive inner feelings, heroism, and divinity). The recommendation from these findings is that multi-stakeholders, including the government, provide support to enhance the program sustainability. This research contributes a model of voluntary teaching for low socio-economic early graders that can be adapted in other locations in Indonesia and overseas.